Heat-Induced Changes of Plastid Pigments in Tobacco Laminas from Different Stalk Positions During Flue-Curing Period - Chu, Dayan; Xie, Yueqin; Yong, Guoping; Yan, Xiangyang; Tong, Hongwu; Liu, Shaomin (Asian Journal of Chemistry, 2010)
This investigation studied the evolution of plastid pigments in tobacco laminas from different stalk positions during flue-curing period with different temperatures. Chlorophyll and carotenoid content, as well as moisture of tobacco laminas, were monitored during the flue-curing period. Data obtained indicated that the majority of plastid pigments degradation occurred during the yellowing stage under relatively lower temperature (36 to 44 ºC). Meanwhile, degradation of individual plastid pigment was found to be inhomogeneous during the flue-curing period and the declines of pigment contents varied from 96.7 % for violaxanthin to 60.6 % for β-carotene. The rate of total chlorophylls degradation being more marked than that of total carotenoids and which was confirmed by the evolution of the ratio of their contents. Different stalk positions also contributed to the degradation content difference in tobacco laminas, with bottom laminas to be the most obvious, followed by top and middle laminas, respectively. While at the end of the flue-curing period, the content of any pigment in top laminas was almost the same as in middle laminas, both higher than that in bottom laminas. It is also observed that, during the fluecuring period, the moisture content in tobacco laminas and the degradation contents of pigments showed a positive correlation. In general, all obtained results demonstrate that the evolution of moisture and plastid pigments contents in tobacco laminas directly depend on the designed flue-curing temperature conditions and a fine control of temperature would help to modulate the degradation of pigments with the aim of improving the quality of flue-cured tobacco laminas.